2013
DOI: 10.1016/j.actatropica.2013.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Raw fish consumption in liver fluke endemic areas in rural southern Laos

Abstract: Consumption of raw or insufficiently cooked fish is a major public health concern in Southeast Asia, and in Lao People's Democratic Republic (Lao PDR), in particular. We aimed to assess the knowledge, attitudes, perceptions and practices of villagers in liver fluke endemic areas related to raw fish preparation, consumption and its health consequences. In February 2010, eight focus group discussions (FGDs, 35 men and 37 women total) and direct observations were conducted in four randomly selected villages in Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 16 publications
0
29
0
Order By: Relevance
“…This result may be related to the dietary behaviour of this group, where raw fish is an ingredient commonly consumed in southern Lao dishes, especially in rural communities (Xayaseng et al, 2013). A majority of parents in the study area permitted their children to eat raw fish when the children were under 10, 15 and 18 years of age.…”
Section: Discussionmentioning
confidence: 93%
“…This result may be related to the dietary behaviour of this group, where raw fish is an ingredient commonly consumed in southern Lao dishes, especially in rural communities (Xayaseng et al, 2013). A majority of parents in the study area permitted their children to eat raw fish when the children were under 10, 15 and 18 years of age.…”
Section: Discussionmentioning
confidence: 93%
“…life stage and agricultural events), where raw fish dishes are a prominent marker of commensality and underline the importance of ethnic and religious belonging [36]. In contrast, Laotheung communities — and many of them adhere to local religious beliefs — do not, in general, engage in the multitude of elaborate ceremonial practices, which include the mandatory consumption of raw or insufficiently cooked fish.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Laoloum people and their villages have a much better, and thus more frequent, access to raw fish and raw fish dishes, particularly at markets, food stalls, in shops and through street vendors, than do the Laotheung who tend to live in somewhat remote areas without well-developed road networks and easy access to urban centres. Direct observation revealed that environmental conditions also contribute to the increased O. viverrini infection rate among the riparian Laoloum people: they live mainly along big rivers and streams with a large fish stock; the abundance of freshwater fish leads to regular consumption of raw fish [36]. In contrast, Laotheung communities live in a mostly hilly and rugged physical environment and do not have this rich quantity and quality of fish in the creeks; consequently, they consume raw fish less frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings to our study are reported in another survey recently conducted in Saravane District, Saravane Province, in southern Laos. Communities believed that after squeezing hundreds of weaver ants -this ant contains a sour juice -over the fish meat this would turn to white colour which was comparable to a well-cooked dish and therefore safe for eating (Xayaseng et al, 2013). In Lao PDR, freshwater fish are infected in high prevalence rates with O. viverrini, H. taichui and other minute intestinal flukes Chai et al, 2007;Chai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%